Relationship Between Religiosity and the Level of Moral Reasoning of High School Student - Fidya Alvi Mufida (Program Studi Psikologi UIN Sunan Ampel Surabaya, 2019)
The purpose of this study was to determine the relationship between religiosity and the level of moral reasoning of high school students. This research is correlation research using data collection techniques in the form of a religiosity scale and moral reasoning scale. The results of this study indicate that there is a relationship between religiosity and students' level of moral reasoning Senior High School, with a correlation coefficient of (-0.049) with a significance of 0.668. This shows that there is no significant relationship between religiosity and the level of moral reasoning of high school students. Based on the negative coefficient price, the higher the level of religiosity followed by the low level of moral reasoning, and vice versa, the higher the level of moral reasoning followed by low religiosity in high school students.